Development Of Protective Oxide Scales On Hastelloy C22 For High Temperature Corrosion In Alkali Salt Environment - Thor, Jin Ann (Universiti Sains Malaysia, 2017)
High temperature corrosion is the major drawback of commercialization of biomass fired power generation due to the chlorine-induced corrosion at high temperature. In order to protect the underneath alloy, the oxidation behavior of Hastelloy C22 at different temperatures (800, 900, 1000 and 1100 °C) was studied in order to develop a protective oxide scale. The oxidation products were investigated in detail via Field Emission Secondary Electron Microscope equipped with Energy Dispersive X-ray Spectroscopy (FESEM-EDX), X-ray Diffraction (XRD) and mass gain measurement. From the results, the protective oxide scale was successfully developed on Hastelloy C22 that was pre-oxidised at 1000 °C. Then, the corrosion behavior of Hastelloy C22 with protective oxide scale and without protective oxide scale in alkali salt environment consisting of 95.5 wt% KCl + 4.5 wt% NaCl were compared and studied. The corrosion test was conducted at 700 °C for 100 hours. The corrosion products were examined via the same characterization as oxidation products, except for the mass gain measurement which was replaced by mass loss measurement due to the spallation of oxide scale. The pre-oxidised Hastelloy C22 exhibits better corrosion resistance than the raw Hastelloy C22 as the oxide scale formed has the ability to prevent the penetration of corrosion reagent into the substrate.